2013
DOI: 10.1159/000351753
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the European and Japanese Guidelines for the Management of Ischemic Stroke

Abstract: Background: Different aspects of acute stroke management and strategies for stroke prevention derive from two viewpoints: specific traditional and historical backgrounds and evidence-based medicine from modern randomized controlled trials (RCTs), meta-analysis and authorized clinical practice guidelines (GLs). Regarding stroke, GLs have been published by national and international organizations in different languages, most frequently in English. Cerebrovascular Diseases published the European GLs for the manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 78 publications
0
31
0
1
Order By: Relevance
“…All participating centers applied IVT/IAT according to wellestablished criteria and guidelines, 7,26 with the exception that, in selected patients, NOAC treatment was not considered an absolute exclusion criterion.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…All participating centers applied IVT/IAT according to wellestablished criteria and guidelines, 7,26 with the exception that, in selected patients, NOAC treatment was not considered an absolute exclusion criterion.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…Argatroban patients were also more likely to receive histamine-2 receptor blockers, which are recommended for use in older patients and patients with severe stroke in the Japanese guidelines for treatment of acute ischemic stroke. 2 This tendency would also indicate that argatroban was used for patients with severe stroke in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The present study analyzed 2289 pairs of patients and suggested that argatroban was not associated with more favorable outcomes at least according to its recommended use in Japan. 2 In the present study, we evaluated the effect of argatroban monotherapy on stroke outcomes. On the contrary, the Argatroban tPA Stroke Study (ARTSS-1) evaluated the safety of argatroban use in combination with r-tPA in patients with ischemic stroke.…”
Section: Strokementioning
confidence: 99%
See 2 more Smart Citations